Exchange-rate discounting - Gregor W. Smith (Queen's University, Department of Economics, 1995)
Economists often describe nominal exchange rates as forward-looking, so that they reflect discounted, expected, future fundamentals. This study applies a method for identifying the discount rate involved, without knowing or measuring fundamentals. Identification arises from assumptions on the stochastic process followed by fundamentals, combined with nonlinearity arising from expected future regime changes. Two applications yield evidence against the present-value model in the form of discount rates which are negative and statistically significant.
Keywords: F32; G12; 330; floating exchange rates; regime switching